Vitamin D status and CYP27B1-1260 promoter polymorphism in hepatitis C virus-infected children and its effect on response to interferon-α-based treatment. Issue 4 (October 2018) - Mowafy, Mohamed; Elsedfy, Heba; Ibrahim, Salah; Humoda, Shaimaa; Mahmoud, Rana A.A.; Abdel Ghaffar, Tawhida Y.
Abstract : Background: Hepatitis C virus (HCV) is a major cause of chronic liver disease with significant morbidity and mortality. Recent evidence suggests that vitamin D through its immunomodulatory, anti-inflammatory, and antifibrotic properties may affect clinical outcomes and treatment response in HCV infection. Aim: The aim was to study the vitamin D status in children with chronic HCV infection and the relation of serum levels of 25-hydroxycholecalciferol (25OHD), 1, 25-dihydroxycholecalciferol [1, 25(OH)2 D], and genetic polymorphism of 1α-hydroxylase (CYP27B1-1260 rs10877012) to the response to interferon-α (IFN-α)-based therapy. Patients and methods: This cross-sectional case-controlled study included 30 children diagnosed with chronic HCV infection who were compared with 20 age-matched, sex-matched, and pubertal stage-matched clinically normal controls. The patients were divided into two groups according to their response to HCV treatment by pegylated IFN-α and ribavirin: responders (10 patients) and nonresponders (20 patients). Anthropometric measurements, clinical examination, abdominal ultrasound, liver biopsy, liver functions, and measurement of HCV RNA by PCR before and after treatment were done for the patients, whereas serum 25OHD level, 1, 25(OH)2 D level, and molecular studies were done for both patients and controls. Results: Compared with controls, patients had significant deficiency of both 25OHD and 1, 25(OH)2 D (30.5±6.7 vs. 60±15.7 ng/ml and 16.77±1.828 vs. 37.17±3.699 ng/ml, respectively; P <0.001). 25OHD levels showed significant negative correlation with the stage of fibrosis in patients ( P <0.05). Only 1, 25(OH)2 D was significantly related to the response to treatment ( P <0.05). The patients with the AA genotype of CYP27B1-1260 rs10877012 tended to have higher serum levels of 1, 25(OH)2 D levels compared with those with AC or CC genotypes, yet this reached significance only among those who responded to treatment. Conclusion: Children with chronic HCV infection have lower levels of vitamin D compared with their normal counterparts. 1, 25(OH)2 D and not 25OHD is related to response to IFN-α-based treatment. CYP27B1 gene polymorphisms may modulate vitamin D metabolism in patients with chronic HCV infection, thus may play a key role in treatment response.